The Correlation between Students’ Habits in Listening English Songs and Their Achievement - Ayuningsih, Putri; Nurindah, Nurindah; Siam, Siam (Journal of Teaching of English, 2022)
The purpose of this research was to find out the correlation between students’ habits in listening to English songs and their listening achievement at the English Education Department of Halu Oleo University. This research was quantitative research and the design used correlational research designs. The population was all of the 2018 academic year students with a total of 128 students, and the sample of this research was 35 students of class A. This research used a questionnaire and students’ listening achievement scores as the instrument. The data were analyzed using descriptive statistics and inferential statistics through IBM SPSS 26 program. The findings of this research show that the majority of the students have habits of listening to English songs and most of them have good achievements in listening. After correlating them, it was found that the value of the correlation coefficient is 0.417 in the significant value of 0.013. From the sig-value seems that there is a significant correlation between the variables. The correlation-value shows that the correlation is positive in the moderate category. So, it can be concluded that there is a significant correlation between students’ habits in listening to English songs and their listening achievement, and the correlation is categorized as a positive and moderate level of correlation.